Transformasi Digital UMKM Platfrom Prototype Berbasis Web Pemesanan dan Logistik - Sinta, Sinta; Magdalena, Hilyah (METIK JURNAL (AKREDITASI SINTA 3), 2025)
Keripik Afacherry is a Micro, Small, and Medium Enterprise (MSME) specializing in various flavors of light snack chips, officially established in 2017. Digital transformation plays a crucial role in enhancing the efficiency and competitiveness of MSMEs in the Industry 4.0 era. This study focuses on developing a web-based platform for ordering and logistics using the Rapid Application Development (RAD) method to address the challenges of the still predominantly manual system. Currently, the business relies on three sales methods: conventional (offline retail), social media, and e-commerce, all of which require manual interactions for stock checking, order confirmation, and payment validation. Using the RAD approach, the system is developed iteratively with key features such as digital payment integration, real-time order tracking, and automated inventory management. The findings indicate that implementing a web-based system can reduce order recording errors, accelerate distribution, and improve operational efficiency and customer satisfaction. Furthermore, digitalized logistics provide benefits in more accurate stock management and optimized delivery processes. Therefore, further development is necessary to enhance data security, optimize the user interface (UI/UX), and conduct sales data analysis to support more strategic business decision-making. The system simplifies previously manual ordering and logistics workflows, reduces the risk of data entry errors through a more structured digital system, and provides a foundational design ready for implementation in MSMEs.. This research is expected to serve as an innovative solution for MSMEs in overcoming digitalization challenges and increasing competitiveness in an increasingly dynamic market